Non-typhoidal Salmonella DNA traces in gallbladder cancer. Issue 1 (December 2016) - Iyer, Prajish; Barreto, Savio; Sahoo, Bikram; Chandrani, Pratik; Ramadwar, Mukta; Shrikhande, Shailesh; Dutt, Amit
Abstract Background We earlier proposed a genetic model for gallbladder carcinogenesis and its dissemination cascade. However, the association of gallbladder cancer and 'inflammatory stimulus' to drive the initial cascade in the model remained unclear. A recent study suggested infection withSalmonella can lead to changes in the host signalling pathways in gallbladder cancer. Findings We examined the whole exomes of 26 primary gall bladder tumour and paired normal samples for presence of 143 HPV (Human papilloma virus) types along with 6 commonSalmonella serotypes (S. typhi Ty2, S. typhi CT18, S. typhimurium LT2, S. choleraesuis SCB67, S.paratyphi TCC, andS. paratyphi SPB7) using a computational subtraction pipeline based on the HPVDetector, we recently described. Based on our evaluation of 26 whole exome gallbladder primary tumours and matched normal samples: association of typhoidalSalmonella species were found in 11 of 26 gallbladder cancer samples, and non-typhoidalSalmonella species in 12 of 26 gallbladder cancer, with 6 samples were found co-infected with both. Conclusions We present the first evidence to support the association of non-typhoidalSalmonella species along with typhoidal strains in gallbladder cancer.Salmonella infection in the chronic carrier state fits the role of the 'inflammatory stimulus' in the genetic model for gallbladder carcinogenesis that may play a role in gallbladder cancer analogous toHelicobacter pylori in gastric cancer.